(untitled) (Journal of Foreign Language Studies, 2022)
The Covid-19 pandemic and its negative impacts forced most educational institutions worldwide to move face-to-face traditional classrooms to online platforms. Online learning has shown significant growth over the last years, yet a limited number of teachers and students are familiar with online learning platforms. This study employs a mixed methods approach to investigate the challenges in studying online via Microsoft Teams encountered by English as a Foreign Language (EFL) students at a public university in Vietnam. The findings show that students faced a number of difficulties when studying on Microsoft Teams, which as a result, affected their learning progress. On that basis, the study offers some pedagogical and research implications for online learning.